(3MLjI GdMce GdUGOQ ai GdOYhi GdOSJhQjI hJfajPg ai GdchjJ (B: s (3OQGSI ebGQfI (B/ s - (3fGja NGdO fGja GdeWjQi s; (3eMeO eMeO HOQGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3JNJda CfXeI GdOhd ai EYeGd GdQbGHI Ydi OSJhQjI GdbhGfjf agfGc ef jYgO HgG Edi LgI bVGFjI hGMOI ceUQ hGdchjJ hefgG eG jYgO HgG Edi LejY GdgjFGJ GdbVGFjI hGdhdGjGJ GdeJMOI GdCeQjcjI gi GdfehPL dPdc hHGdJGdi aEf GdCeQ GdeJQJH Ydi GdMce GdUGOQ ai GdOYhi GdOSJhQjI jNJda HGNJdGa GdCfXeI aefgG eG jDOi Edi EdZGA GdJTQjY hefgG eG jcJai HJbQjQ YOe GdOSJhQjI hef Ke GdGeJfGY Yf GdJfajP (B. (3cPdc aEf GdGNJdGa jTed CjVG GdMLjI aHYVgG jbQQ GdMLjI GdeWdbI eKd GdchjJ heUQ hHYVgG GdMLjI GdfSHjI ceG gh ai GdfXGe GdCeQjci cPdc jTed gPG GdGNJdGa GdeOi GdRefi ddMce aHYVg jLYdg PG CKQ ahQi ceG gh GdTCf ai HYV GdCMcGe GdOSJhQjI ai eUQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B395-419s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3efGRYGJ GdJfajPs; (3GdbGfhf GdebGQf s; (3GdchjJ s; (3GdMce GdbVGFjs; (3MLjI GdGMcGes; (3GdMce GdOSJhQjs; (3GdeOi GdRefjs; (3WQb GdWYfs; (3GdOYhi GdOSJhQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes